Pengembangan Buletin IPA Tema Pangan Sebagai Sumber Energi Berbasis Contextual Teaching and Learning (CTL) Yang Berorientasi Pada Kemampuan Berpikir Kritis - Dwita Apriliawati; Suroso Mukti Leksono; Liska Berlian (UNIB Press, 2022)
This research was motivated by the lack of development of innovative contextual-based learning media. The aims of this research were (1) to develop a food theme science bulletin as an energy source based on Contextual Teaching and Learning (CTL) which is oriented towards critical thinking skills, and (2) to determine the feasibility level of a food theme science bulletin as an energy source based on Contextual Teaching and Learning (CTL) which is oriented towards critical thinking skills. The method used was research and development of a 4-D model modified by Thiagaradjan. The research was conducted in 3 stages: define, design, and develop. The instrument used was a validation sheet which is validated by expert lecturers and junior high school science teachers. The results showed that (1) the process of developing a science bulletin was carried out using three stages of the 4-D model, such as define, namely problem identification, design, namely producing products and instruments, and developing stage, namely obtaining product feasibility, (2) feasibility level of food science bulletins. as an energy source based on Contextual Teaching and Learning (CTL) oriented to critical thinking skills, it gets a very decent category from material experts and media experts, each getting a percentage of 87.48%, for material experts and 91.40% for media experts. Based on the overall validation value, if on average it gets a percentage of 89.44% in the very feasible category, so that science bulletins can be used as learning media and can be tested in science learning in schools.